Is the Complement Protein C1q a Pro- or Anti-tumorigenic Factor? Bioinformatics Analysis Involving Human Carcinomas - Mangogna, Alessandro; Agostinis, Chiara; Bonazza, Deborah; Belmonte, Beatrice; Zacchi, Paola; Zito, Gabriella; Romano, Andrea; Zanconati, Fabrizio; Ricci, Giuseppe; Kishore, Uday; Bulla, Roberta (Frontiers in Immunology, 2019)
C1q is the first subcomponent of the classical pathway of the complement system and belongs to the C1q/Tumour Necrosis Factor superfamily. In addition, C1q can perform a diverse range of immune and non-immune functions in a complement-dependent as well as -independent manner. Being a charge pattern recognition molecule of the innate immunity, C1q can recognise a number of self, non-self and altered-self ligands and bring about effector mechanisms designed to clear pathogens via opsonisation and inflammatory response. C1q is locally synthesised by macrophages and dendritic cells, and thus can get involved in biological processes such as angiogenesis and tissue remodelling, immune modulation, and immunologic tolerance. The notion of C1q involvement in the pathogenesis of cancer is still evolving. C1q appears to have a dual role in cancer: tumour promoting as well as tumour-protective, depending on the context of the disease. In the current study, we performed a bioinformatics analysis to investigate whether C1q can serve as a potential prognostic marker for human carcinoma. We used the Oncomine database and the survival analysis platforms Kaplan-Meier plotter. Our results showed that high levels of C1q have a favourable prognostic index in basal-like breast cancer for disease-free survival, and in HER2-positive breast cancer for overall survival, while it showed a pro-tumorigenic role of C1q in lung adenocarcinoma, and in clear cell renal cell carcinoma. This in silico study, if validated via a retrospective study, can be a step forward in establishing C1q as a new tool as a prognostic biomarker for various carcinoma.